Sommer Atelier : Junge Kunst in Europa (München : Klinkhardt & Biermann, 1990)
Bergmann, Franz ; Blanckart, Olivier ; Buts, Thomas ; Christensen, Jeanette ; Dau, Mila ; Drebber, Magdalena ; Fomski ; Gauss, Heidemarie ; Grilo, António Manuel ; Hübner, Teodóra ; Kempff, Peter ; etc.
Sommer Atelier : Junge Kunst in Europa, Messeplatz Hannover, 1990. More than 300 young artists from throughout Europe will come together here to produce works and, in dialogue with the public, achieve a level of communication that goes beyond national boundaries.
boek
Keywords: Europa